THE EFFECTS OF INTERNATIONAL TRADE ON INTERNATIONAL MONEY LAUNDERING FROM THE PERSPECTIVES OF INTERNATIONAL LAW AND INTERNATIONAL TRADE IN TURKEY - Zelha Altinkaya; Ozlem Yucel (European Scientific Journal, ESJ, 2014)
Globalization has influences on economies of all countries. Not only the capital but commodities became very important part of global mobility. Many countries tried to cooperate and collaborate to adopt their own national law and principles for both capital mobility and commodity mobility. However, in international trade, there are observations about trade of either illegal goods or trading international but caused to international money laundering. This paper will analyse money laundering mechanism based on the trade of goods and services, commonly known as trade based money laundering. Specifically, Turkey will be the specific case.